Quality of Life in Psoriasis: A Cross-Sectional Study from North India - Khushboo Arora; Neirita Hazarika; Ranjeeta Kumari; Himanshu Chawla (Indian Journal of Dermatology)
Background: Psoriasis is a chronic inflammatory papulo-squamous disease characterized by multiple remissions and relapses. This study aimed to assess the impact of psoriasis on the quality of life of patients. Materials and Methods: A hospital-based, cross-sectional study was conducted enrolling 198 adult patients of psoriasis. The STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines for observational studies were followed. Clinical severity of psoriasis was measured using Psoriasis Area Severity Index (PASI), and quality of life was measured by EuroQoL 5D (EQ-5D-5L, EQ-VAS) and Psoriasis Quality-Of-Life-12 (PQOL-12) Questionniares. Results: Of the 198 patients, 71.7% (n = 142/198) were males with a mean age of 41.65 ± 13.19 years. The mean PASI score was 12.46 ± 11.51, and the mean PQOL-12 score was 50.18 ± 23.36. Up to 22.7% (n = 45) cases had ‘severe’ and 6.1% (n = 12) cases has ‘very severe’ PQOL-12 scores. Statistically significant correlation (P < 0.05) was observed between PASI scores and almost all domains of EQ-5D-5L and PQOL-12. Conclusion: Psoriasis affects most psycho-social domains of a patient’s life. Coping with these QOL issues remains a challenge to the patients in everyday life. The goal of management of psoriasis therefore must include measures to improve quality of life along with long-lasting remittance of physical symptoms.